Research into the impact of structural features of combustion chamber in energytechnological units on their operational efficiency - Nikolsky, V.; Нікольський, В.; Oliynyk, О.; Олійник, О.; Ved, V.; Вед, В.; Pugach, А.; Пугач, Андрій Миколайович; Turluev, R.; Турлуєв, Р.; Alieksandrov О.; Олександров, О.; et al. (Open Journal Systems (OJS), 2018)
Experimental studies of the influence of the degree of masonry (geometry) and aerodynamics of the fire chambers (evacuation schemes of combustion products) on the energy technological parameters of processes in the gas-solid system (in the furnace chambers) have been fulfilled. At the industrial large-scale fire stand, experimental studies were carried out on the influence of the geometry and aerodynamics of the combustion chamber on the energy-technological parameters in the gas-solid system. It is shown that the decrease in the height of the working space of the combustion chamber, equipped with flat flame burners, affects the use of fuel due to the intensification of heat transfer, including direct convection. The dependence is caused by the reduction of heat losses from the source gases, as well as by reducing heat losses through the laying. It is established that at a height of the working space of 800 ÷ 1000 mm of combustion chamber with flame burners there is a reduction of fuel consumption by 20 ÷ 30%. The design of the furnace space of the continuous furnace furnace has been developed. A distinctive feature of the design of the furnace is the elimination of discreteness and the implementation of a stable continuous mode of operation of the heat aggregate. Виконано експериментальні дослідження впливу ступеня розвитку кладки (геометрії) і аеродинаміки топкових камер (схеми евакуації продуктів згоряння) на енерготехнологічні показники процесів в системі газ-тверде тіло (в топкових камерах). На промисловому великомасштабному вогневому стенді проведені експериментальні дослідження впливу геометрії і аеродинаміки топкової камери на енерготехнологічні показники в системі газ-тверде тіло. Показано, що зменшення висоти робочого простору камери згоряння, обладнаної плоскополум’яних пальниками, впливає на паливовикористання за рахунок інтенсифікації теплообміну, в тому числі прямій конвекції. Залежність обумовлена зменшення втрат тепла з вихідними газами, а також за рахунок зменшення втрат теплоти через кладку. Встановлено, що при висоті робочого простору 800÷1000 мм камери згоряння з плоскополум’яними пальниками відбувається скорочення витрат палива на 20÷30 %. Розроблено конструкцію топкового простору печі безперервного режиму роботи. Відмінною особливістю печі розробленої конструкції є ліквідація дискретності і реалізація стабільного безперервного режиму роботи теплоагрегату.
Дослідження впливу конструктивних особливостей камери згоряння в енерготехнологічних установках на їх експлуатаційну ефективність
Keywords: combustion chamber; камера згоряння; heat exchange; теплообмінv; fuel consumption; витрати палива; aerodynamics; аеродинаміка; flame burner; плоскополум’яний пальник; tunnel furnace; тунельна піч; temperature of combustion products; температура продуктів згоряння